2020
DOI: 10.3390/ijerph17165968
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Respirator Literature and a Survey among Dental Professionals

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus was discovered in China in late 2019 and subsequently triggered a global pandemic. Dentists, like many other health professionals, are at an increased risk of contracting the virus as they work in close proximity to patients, especially when performing aerosol-generating procedures. Thus, in order for dentists to protect themselves and their patients, it is recommended that practitioners wear filtering facepiece 2 (FFP2) respirators. The prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…Also, breathing discomfort due to N95 face mask has also been reported in the literature confirming our finding that dyspnoea is a common adverse event among HCWs due to PPE use [52][53][54]. Α survey among dental professionals during the COVID-19 pandemic found that the prolonged use of filtering facepiece 2 (FFP2) respirators was related with moderate breathing difficulties [55]. Moreover, increased levels of anxiety and stress among HCWs during the pandemic [56,57] may contribute to breathing difficulties.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, breathing discomfort due to N95 face mask has also been reported in the literature confirming our finding that dyspnoea is a common adverse event among HCWs due to PPE use [52][53][54]. Α survey among dental professionals during the COVID-19 pandemic found that the prolonged use of filtering facepiece 2 (FFP2) respirators was related with moderate breathing difficulties [55]. Moreover, increased levels of anxiety and stress among HCWs during the pandemic [56,57] may contribute to breathing difficulties.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, isolation gowns cover the entire body causing heavy sweating and continuous dehydration especially among smokers and obese individuals. A scoping review [55] among dental professionals has revealed moderate breathing difficulties due to the use of filtering facepiece 2 respirators, while the prolonged duration of respirators usage was related with headaches. This finding is confirmed by a study [46] that was conducted during the SARS pandemic and found that 37.3% of HCWs who were N95 face-masks developed headaches.…”
Section: Discussionmentioning
confidence: 99%
“…As we expected, the score for fear of COVID-19 was correlated with the practice of preventive measures, meaning that the higher the score was, the more preventive measures were applied. Even if studies identified that the use of FFP2 masks was associated with headaches (47.5%), severe exertion and discomfort (50.8%), moderate concentration problems (54.3%), moderate breathing difficulties (63.5%), and impaired work ability (85.5%) as Farronato et al [ 41 , 42 ] showed in their studies, protective behaviors were adopted by all dentists and considered fundamental in protecting dentists and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…In countries with cultural norms or government policies supporting public mask-wearing, per-capita coronavirus mortality increased on average by just 16.2% each week, as compared with 61.9% each week in the remaining countries [ 7 ]. For example, many young people are more liberal, and they consider wearing a mask to be a restriction on their freedom and not in line with traditional attitudes [ 8 , 9 ]. Wearing masks is meaningful, but there are still some people who do not wear masks on their daily trips.…”
Section: Introductionmentioning
confidence: 99%